(untitled) (International Journal of Mathematics and Physics, 2018)
This paper studies solitary wave solutions of a generalized nonlinear Klein-Gordon (KG) equation with power-law nonlinearity via the so-called first integral method. Using the method, some soliton solutions of the equation are obtained. The method is hereby shown to be an efficient and reliable mathematical tool for solving many nonlinear evolution equations arising in a number of problems in science and engineering. undefined undefined Звуковая функция ограничена 200 символами Настройки : История : Обратная связь : Donate Закрыть